Illegal Labor Migrants Management complying with Government’s Policy in Samut Sakhon Province. - Sasing, Nattawan; Phothikun, Anan (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
This research aims to study “Illegal Labor migrants Management complying with The Thai government Policies in Samut Sakhon Province” The objectives of which are ; to investigate the problem of the management of illegal labor migrants management complying with the Thai government policies in Samut Sakhon province, to study the on-going implementation of the government’s policies regarding illegal labor migrants in Samut Sakhon province, and to study about problems and barriers affecting the management of illegal labor migrants management complying with the Thai government policies in Samut Sakhon province. A critical realism paradigm and qualitative method were employed. In-depth interviews were conducted with various experts working for either government or private sectors using a semi-structured interview guide. Government officers interviewees were those who worked for Department of Employment, Office of Foreign Welfare Administrative, Immigration Bureau, Provincial Police Office, Department of Labor Protection and Welfare, Ministry of Social Development and Human Security, together with interviewees from products industrial companies, fisheries companies. The data was analyzed systematically and theoretically which largely inductive and interpretative. The research findings indicate that 1. The management of illegal labor migrants management was to grant and legalize them, to provide them wages and other employment conditions and benefits as well as to grant them all legal documentations, to allow their family members to follow them and to launch the new measurement importing new legal labor migrants to suit the appropriate actual numbers of provincial labor market’s need. 2. The Implementation of pre-determined policies in the context of Samut Sakhon province by arresting those who illegally acted against the laws and at the same time applying the amnesty processes was synchronizing completed. But, the cooperation from employers’ registering their migrant employees was still limited in number. 3. Problems and barriers affecting the management of illegal labor migrants management complying with the Thai government policies in Samut Sakhon province were; The policies were not clearly stated enough to be implemented effectively. Yet, too many details and conditions to be considered unavoidably. Furthermore, the Thai government did not strongly and fully support in many aspects, especially information needed that employers were not assured to follow those policies. Besides, the perceptions of the front-line officers were poor regarding to the existing of human trafficking in the area. Lastly, decision making, further planning and policies implementation evaluating were poor due to inadequate budget, information technological support system which affecting the controlling and problem solving effectively. These research findings suggest that the policies implementation will be more successful with effectiveness and better concrete result in the future if the management of illegal labor migrants in Samut Sakhon province has more specific direction and appropriate policies implementation in comply with the Thai government’s policies. The management should monitor labor registering processes closely, collaborating with other functions concerned for more information and the sharing of necessary resources especially budget, tools and equipment. Finally, the management has to make sure that what they are doing is known to all people in the area. Article history : Accepted 22 July 2016 SIMILARITY INDEX = 1.55